Economic-environmental energy supply of mobile base stations in isolated nanogrids with smart plug-in electric vehicles and hydrogen energy storage system - Bahri, Reza; Zeynali, Saeed; Nasiri, Nima; Keshavarzi, Mohamad Reza (International journal of hydrogen energy, 2023)
The mobile base stations (MBS) are fundamental communication devices that ensure the constant stream of interconnectivity. However, they are mostly installed in off-grid regions. This study investigates the economic-environmental energy supply of a MBS in an isolated nanogrid (ING) that also includes a hydrogen energy storage system (HES), photovoltaic (PV) system, controllable plug-in electric vehicles (PEV) and a diesel generator (DG). A novel mixed-integer second-order cone programming (MISOCP) formulation is proposed to capture the nonlinearities of the various components through a convex optimization model. The study included different uncertainties including the traffic rate of the MBS, driving schedule of the PEVs, and PV generation via a hybrid stochastic programming (SP) and robust optimization (RO) methods. The influence of the coordinated PEV charging strategy, risk-averse RO and multi-objective optimization was studied through various case studies. The outcomes show that coordinated PEV-charging can have a significant contribution in reducing the risks and curtailing both cost and emission objective functions, while using economic-environmental operation model can cut the emissions by 17.70%. •An economic-environmental energy supply framework for mobile base stations.•The impact of coordinated plug-in electric vehicle charging is scrutinized.•A mixed-integer second-order cone programming approach is deployed.•The uncertainties in communication traffic, PV generation and behavioural patterns of PEVs are modelled.•The proposed model leads to 17.7% lower emission in isolated nanogrids.